Effectiveness of a health literacy intervention to improve diabetes outcomes in rural family medicine clinics: a randomized pragmatic trial - Laura M. Curtis; Terry C. Davis; Connie L. Arnold; Jennifer M. Gan; Jean C. McSweeney; Scott Hur; Mary J. Kwasny; Michael S. Wolf; Kristie Hadden (Health Literacy and Communication Open)
Background Adults with diabetes mellitus (DM) living in rural areas often face limited access to medical and specialist care, minimal exposure to diabetes education, and transportation challenges. Rural residents also tend to be older, poorer, less educated, under-insured and have lower health literacy compared to their urban counterparts.Aims We tested the effectiveness of the American College of Physicians (ACP) diabetes health literacy intervention in rural community clinics to improve a range of diabetes-related patient outcomes and determine whether the intervention reduces disparities by health literacy.Methods We recruited 756 English-speaking adults with uncontrolled Type 2 DM from rural clinics in Arkansas. Trained health coaches reviewed the ACP Diabetes Guide and conducted counseling and action-planning monthly to participants randomized to the intervention. The enhanced usual care (EUC) arm received an American Diabetes Association workbook and was followed as usual. Interviews were conducted at baseline, 3 and 6 months, and clinical outcomes, including hemoglobin A1C and blood pressure values, were extracted from charts through 12 months post-baseline. Health literacy was measured at baseline using the Newest Vital Sign (NVS). Our primary outcome was A1C at 6 months, with other clinical values and self-reported diabetes-related knowledge, self-efficacy, distress, and self-care behaviors examined as secondary outcomes.Results Participants had a mean age of 55.8 (SD = 11.7), 68% were female, two-thirds had an annual household income <$15,000, and 52% had limited health literacy. Overall, the intervention had little effect on outcomes at 6 and 12 months, including our primary outcome of A1C at 6 months (Intervention Least Squared Means (LSM) 8.28, 95% CI 8.11, 8.46; EUC LSM 8.44, 95% CI 8.26, 8.61). Diabetes knowledge was greater in those with adequate (LSM 9.46, 95% CI 9.25, 9.67) compared to those with limited health literacy (LSM 8.11, 95% CI 7.91, 8.23, p < 0.001) at baseline. This disparity remained in the EUC arm after 6 months but disparities were mitigated in the intervention arm (interaction p < 0.001).Discussion Our intensive intervention was well received, but insufficient to improve outcomes. Strategies may need to attend to other barriers faced by rural patients beyond health literacy to improve health behaviors and outcomes.